Pengaruh Gaya Kepemimpinan Dan Iklim Organisasi Terhadap Kinerja Karyawan Pada PT. Grand Dafam Bela Ternate - Mahengkeng, Shintia; Husen, zulaiha (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Khairun, 2022)
ABSTRACTObjective: The purpose of this study are: (1) Knowing and analyzing the influence leadership style on employee performance; (2) Knowing and analyzing the influence of organizational climate on employee performance; and (3) Knowing and analyzing the effect of leadership style and organizational climate on the performance of employees at the of PT. Grand Dafam Bela Ternate. The number of research samples was 67 employees at the PT. Grand Dafam Bela Ternate.Methodology: The test equipment used is multiple linear regression analysis (multiple regression) using statistical package for social scientists (SPSS) as a statistical test tool.Finding: H1, H2, and H3 H1 accepted at the 5% confidence level.Conclusion: The results showed that: (1) Leadership Style had a positive and significant effect partially on employee performance at PT. Grand Dafam Bela Ternate. The results of this study mean that, a good leadership style, can improve employee performance; (2) Organizational Climate has a positive and partially significant effect on employee performance at PT. Grand Dafam Bela Ternate. The results of this study mean that a good organizational climate can improve employee performance; and (3) leadership style and organizational climate simultaneously have a positive and significant effect on employee performance at PT. Grand Dafam Bela Ternate.Ã‚Â